Wiley Encyclopedia of Chemical Biology 2008
DOI: 10.1002/9780470048672.wecb649
|View full text |Cite
|
Sign up to set email alerts
|

Hemozoin: A Paradigm for Biominerals in Disease

Abstract: Biomineralization is the formation of organic–inorganic composites by organisms. Originally evolved as a protective mechanism, this complex process has also become a recognized contributor to several disease states, which range from kidney stone disease (nephrolithiasis) to parasitic diseases like malaria. The characteristic three‐step process for the formation of biominerals is defined by the supramolecular preorganization of a nucleating template, the interfacial molecular recognition of crystal nuclei and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Paradigms from the field of biomineralization suggest that the process involves the supramolecular preorganization of an organic matrix (e.g. lipids or proteins) that provides a foundation for the second order assembly for inorganic species1, 38. In malaria, a growing body of evidence suggests that a lipid rich environment is essential for the formation of haemozoin1216.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradigms from the field of biomineralization suggest that the process involves the supramolecular preorganization of an organic matrix (e.g. lipids or proteins) that provides a foundation for the second order assembly for inorganic species1, 38. In malaria, a growing body of evidence suggests that a lipid rich environment is essential for the formation of haemozoin1216.…”
Section: Resultsmentioning
confidence: 99%
“…lipids or proteins) that provides a foundation for the second-order assembly for inorganic species. 1, 38 In malaria, a growing body of evidence suggests that a lipid-rich environment is essential for the formation of haemozoin. 12-16 However, previous experimental data for bhaematin formation under physiological conditions could not account for the speed of haemozoin formation in vivo or provide details of the nucleation and crystal extension process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been a revival of interest in the aqueous solution chemistry of free ferriprotoporphyrin IX [Fe(III)PPIX; ferriheme]. This arises from its implication in heme acquisition by both mammalian and bacterial cells and more especially heme detoxification in the malaria parasite and in other blood-feeding organisms. For many years it was assumed that Fe(III)PPIX spontaneously forms a μ-oxo dimer, μ-[Fe(III)PPIX] 2 O, as the dominant species in aqueous solution . However, over the last 5 years three studies have clearly demonstrated that this is not the case. Rather, in pure aqueous solution, it exists as a π–π dimer of H 2 O–, HO–Fe(III)PPIX or a dimer comprising one of each species, depending on pH .…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantially larger contribution of charge transfer transitions in μ-[Fe(III)-PPIX] 2 O compared with H 2 O−Fe(III)PPIX in this part of the spectrum. The major contributing transitions are CT(7) and CT(8), which are π→d π transitions and CT(12), which is a π→d z 2 transition. The high energy shoulder of the Soret peak will not be discussed further, owing to the very large number of underlying excitations (see Scheme 2).…”
mentioning
confidence: 99%
“…ART contains an endoperoxide bridge (R-O-O-R') that is required for its anti-malarial activity. Malaria parasites digest hemoglobin as a carbon source, and accumulate a large amount of iron [8][10]. When ART encounters an iron atom, the endoperoxide group breaks up, and forms free radicals.…”
Section: Introductionmentioning
confidence: 99%